The Quality of life - Nussbaum, Martha Craven, 1947-; Sen, Amartya Kumar (Studies in development economics., 1993)
The idea of the quality of life is central to economic and social assessment and also to public policy, social legislation, and community programmes. However, the commonly used indicators of economic success such as per capita income are at best crude measures of the quality of life. There is a strong need for a systematic exploration of the content, reach, and relevance of the concept of the quality of life, and ways of making it concrete and usable. In this collection of essays, some leading economists and philosophers rise to that challenge and provide a wide-ranging investigation. The essays include examination of recent attempts to replace incomes and utilities by the concept of capability and also exploration of the classic Aristotelian accounts of human flourishing, which provide insights into capability-based assessment of the quality of life. Some underlying methodological problems are also examined, including cultural relativism and utility as a measure of advantage. Possibilities of application are discussed in the context of important practical problems, such as correcting gender-based inequalities, determining medical priorities, and promoting living standards. The overall result is a major contribution to the understanding and use of the idea of the quality of life.